Peran Balneoterapi pada Psoriasis - Putri Oktriana Rachman; Budi Eko Prasetyorini; Nathania Amelinda; Fatimah Fitriani; Arie Kusumawardani (MEDICINUS, 2022)
Psoriasis is a chronic recurrent inflammatory disease influenced by several risk factors, including genetics, immune system, environment, and hormones. Skin lesions associated with psoriasis are well-defined erythematous plaques covered in thick, layered, white scales. Psoriasis treatment varies according to the severity of the condition and may include topical or systemic medications, light therapy, or natural elements such as minerals and balneotherapy. Balneotherapy may be used in conjunction with other treatments for psoriasis due to its efficacy in healing psoriasis lesions, particularly plaque forms. Balneotherapy is a traditional medicinal treatment that involves bathing, drinking, or inhaling mineral-containing water. Mineral sources include mineral water, mineral mud (peloids), and natural gas from natural springs. Balneotherapy can thin the stratum corneum and lucidum, decrease the number of lymphocytes, histiocytes, granulocytes, and eosinophils, increase skin permeability, decrease inflammation, improve microcirculation and the skin immune system, and decrease pro-inflammatory cytokines in psoriasis. This article aims to explore the efficacy of balneotherapy as adjuvant therapy for psoriasis to accelerate clinical improvement and reduce disease recurrence.